Non-Acetaminophen Induced Acute Liver Failure of Viral etiology: Treatment with and without NAcetylcysteine; comparing the length of hospital stay and survival status in children at the tertiary care hospital - Parkash, Arit; Asghar, Mohammad; Haider, Nighat (Infectious Diseases Journal of Pakistan, 2023)
Background: Acetaminophen poisoning is a common cause of acute liver failure (ALF) and is treated with N-Acetylcysteine (NAC), which acts as an antidote, antioxidant and anti-inflammatory agent. NAC role in non-acetaminophen induced acute liver failure among children remains controversial and a few centers have adopted this option. Viral hepatitis (A and E) remains the leading cause of ALF in Pakistan. We aim to determine the role of NAC in ALF secondary to viral etiology. Methodology: We performed this quasi experimental study at National Institute of Child Health, Karachi from December 2013 to December 2014. All Children of either gender between ages 5 to 13 years presented with viral induced ALF were enrolled. Children treated with NAC were included in group A and children not given NAC were enrolled in group B. NAC was administered as a continuous intravenous infusion (100 mg/kg/24 hours) until normalization of the INR or death. Standard care treatment was similar throughout the study period. The two groups were compared for the length of hospital stay, discharged or death. Results: There were total 32 patients with 22 males and 10 females. Causes of ALF were HAV 23 (72%), Non A to E 5 (16%), HBV 3(9%) and both A and E in a patients. In group A, all 16 patients received NAC for median duration of 15.5 days. Length of hospital stay in group A was 14.4±6.7 days (median 15.5, IQR(11): 7.5 days to 18.5 days) while in group B it was 23.8±4.1 days (median 24, IQR(8): 19.5days to 27.5 days) pvalue 0.001. Survival was higher in those who received NAC 11 (69%) than those who did not receive 7 (44%) but there was no statistically significant relationship was observed (p-value 0.154). Overall mortality was found 44% (14 expired out of 32 patients). Conclusion: There was no significant difference in overall survival of patients treated with NAC and without NAC. There was a significant improvement in survival observed in patients with early stage of encephalopathy grade 1& 2 treated with N-Acetylcysteine. Keywords: Length of hospital stay, Survival status, N-Acetylcysteine, Acute liver failure